Peningkatan Pemahaman Generasi Z (Sma Pgri 4 Padang) Tentang Pentingnya Partisipasi Aktif Dalam Memilih Guna Mewujudkan Indonesia Maju Dan Berdaulat - Nami, Cici Putri; Zahra N.H, Fatima; Agustiani, Tri; Mulyadi, Dede; Zalfaro, Farhan; Putri, Uci Asriadi; Rahman, Aulia; Juwita, Putri; Sovya Sy, Armina Aya; Widi S, Azella; Pratiwi, Aulia Gading; ., Nopaluwis; Marwenny, Elwidarifa (GLOBAL SCIENTS PUBLISHER, 2026)
Generation Z currently dominates the voter composition within Indonesia's demographic structure, making their role a primary determinant in realizing the vision of an Advanced and Sovereign Indonesia 2045. However, the sheer number of young voters is not proportional to the depth of their political literacy. This paper aims to analyze the urgency of increasing Generation Z's understanding of active participation in general elections. The main issues addressed include high levels of political apathy, the influence of echo chamber phenomena on social media, and the threats of the post-truth era and money politics that can distort rational choices. Through a literature review and analysis of contemporary situations, it is found that the active participation of Generation Z is not merely the exercise of voting rights, but a strategic investment to safeguard national sovereignty and ensure the stability of development policies. A creative, adaptive, and digital-based transformation of political education is required to bridge the gap between digital native characteristics and civic awareness. In conclusion, strengthening political understanding among Generation Z is the primary key to producing leadership with strong legitimacy to lead Indonesia in the global arena.